2007
DOI: 10.1111/j.1365-2133.2007.08058.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B reactivation: a word of caution regarding the use of systemic glucocorticosteroid therapy

Abstract: Background The potentially fatal complications associated with viral hepatitis B (HBV) reactivation have not been characterized in bullous/connective tissue disease patients receiving prolonged systemic glucocorticosteroids (GCs). Objectives This study reports HBV reactivation following GC therapy for a case series of pemphigus vulgaris and dermatomyositis. Methods The retrospective study cohort comprised 98 patients who received at least 6 months of systemic GC therapy. Results Four cases of HBV carriers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 18 publications
0
29
0
3
Order By: Relevance
“…In vivo, glucocorticoid therapy in CHB patients may result in activation of latent infection, increasing levels of HBV markers and increasing the severity of liver disease, implying that glucocorticoids are involved in HBV replication and gene expression (26). In vitro, glucocorticoid can increase the production of HBsAg, HBeAg and viral RNAs, mediated through specific GRs, in HBV-transfected human hepatoma cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, glucocorticoid therapy in CHB patients may result in activation of latent infection, increasing levels of HBV markers and increasing the severity of liver disease, implying that glucocorticoids are involved in HBV replication and gene expression (26). In vitro, glucocorticoid can increase the production of HBsAg, HBeAg and viral RNAs, mediated through specific GRs, in HBV-transfected human hepatoma cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [62] identified in a retrospective study, four cases of viral hepatitis flares in HBV carriers, who received at least 6 mo of high doses of systemic corticosteroid for connective tissue diseases [62] , and resulted in a mortality of fifty percent.…”
Section: Hbv Reactivations In Patients With Inflammatory Diseasesmentioning
confidence: 99%
“…Cheng et al [58] Autoimmune diseases Case report 2 CHB (1) RS (1) No 2 Nakanishi et al [57] Polymyositis Case report 1 CHB No 1 Zanati et al [59] Mixed connective tissue disease Case report 1 CHB No 1 Bae et al [60] Rheumatoid arthritis Case report 1 CHB No 1 Li et al [61] Idiopathic nephrotic syndrome Prospective 41 CHB (41) No 21 Yang et al [62] Connective tissue disease Retrospective 98 CHB (21) Not applied (77) No 4 Loras et al [39] IBD Retrospective 25 CHB No 6…”
Section: Hbv Reactivations (N )mentioning
confidence: 99%
“…Potential hazards may also indirectly result from drugs used to contrast unfavorable complications of dermatological treatment regimens, such as reactivated tuberculosis necessitating isoniazid or rifampicin administration. Also, unsurveyed administration of immunomodulating/immunosuppressive agents, ranging from corticosteroids to TNF-α antagonists, may be also associated with exacerbation of an underlying chronic viral hepatitis [125][126][127].…”
Section: Virus-related Liver Hazards Related To Treatment Of Skin Dismentioning
confidence: 99%
“…An additional case, related to infliximab, was reported in the results of a questionnaire-based survey involving a nationwide sample of physician members of the American Academy of Dermatology in 2011 [145]. As for nonbiologic treatment-related events, a retrospective study carried out on ninety-eight patients undergoing prolonged corticosteroid treatment for psoriasis-unrelated skin conditions (namely, pemphigus vulgaris and dermatomyositis) showed only four cases of HBV reactivation, two of whom had a fatal outcome [125].…”
Section: Hbv Settingmentioning
confidence: 99%